Critical mass : weighing in on force transformation & speed kills post-operation Iraqi freedom - Lim, Irvin Fang Jau (2009)
Wars are won at the operational and strategic level. And equally important, force structuring decisions made at the highest policy levels that drive the overall force capability development of any military are also critically shape force-fighting orientation and by corollary future mission success. In distilling the lessons of the recent Gulf War II, it is important not to overstate the commonplace observation that speed overdrive by way of 'knowledge-driven' time-sensitive targeting through the use of high-tech weaponry increasingly substitutes the need for mass in the final force-combat power equation. Ignoring the right lessons and learning the wrong ones can result in disastrous mental Maginot lines in force structure and doctrine development. Deadly striking speed without sufficient mass to sustain any war effort up to and beyond culminating point can result in hollow forces with fatal consequences.